2016
DOI: 10.1128/jvi.00419-16
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Spontaneous Control of HIV-1 Is Related to Low Frequency of Infected Cells and Inefficient Viral Reactivation

Abstract: HIV establishes reservoirs of infected cells that persist despite effective antiretroviral therapy (ART). In most patients, the virus begins to replicate soon after treatment interruption. However, a low frequency of infected cells at the time of treatment interruption has been associated with delayed viral rebound. Likewise, individuals who control the infection spontaneously, so-called HIV-1 controllers (HICs), carry particularly low levels of infected cells. It is unclear, however, whether and how this smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 56 publications
(71 reference statements)
6
43
0
Order By: Relevance
“…Recent publications also indicate that the size of the HIV-1 reservoir measured by total cell-associated HIV-1 DNA correlates positively with the frequency of positive recovery measurements in response to various latency-reversing agents20. Additionally, the low frequency of infected cells in the HIV-1 controllers is associated with less efficient viral reactivation21. Our data are in line with these findings indicating that limited reactivation could be a consequence of lower integration events.…”
Section: Discussionsupporting
confidence: 89%
“…Recent publications also indicate that the size of the HIV-1 reservoir measured by total cell-associated HIV-1 DNA correlates positively with the frequency of positive recovery measurements in response to various latency-reversing agents20. Additionally, the low frequency of infected cells in the HIV-1 controllers is associated with less efficient viral reactivation21. Our data are in line with these findings indicating that limited reactivation could be a consequence of lower integration events.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were recently reported by Kiselinova et al (11). More recently, Noel et al also reported that the low level of total HIV DNA in cells from long-term nonprogressors (LTNPs) correlated with the low efficiency of virus production after activation ex vivo (58).…”
Section: Dna Load In Resting Cd4supporting
confidence: 76%
“…Although overall, strong CD8 + T cell-mediated HIV-2 suppression is observed in HIC2 patients, some heterogeneity, as in HIC1, is observed in these patients (39,(49)(50)(51). The absent or low CD8 + T cell-mediated HIV-2 suppression in four patients may be due to several factors.…”
Section: Discussionmentioning
confidence: 78%
“…However, we have previously shown that suppressive CD8 T cell activity in HIV-1 controllers remained low in some donors even when autologous virus was used (39). Alternatively, the absence of suppressive activity may be a consequence of the stringent control of viremia, resulting in the contraction of the HIV-2-specific CD8 + T cell response to a small pool of high-quality memory cells that fall below the detection threshold of our assay (49,52,53). Moreover, we were only able to analyze the CD8 + T cell response in blood and would not be able to measure more robust responses that were active locally in patient tissues (54).…”
Section: Discussionmentioning
confidence: 81%